The superficial zone of articular cartilage - Taku Saito (BMC, 2022)
Abstract The superficial zone of articular cartilage contributes to smooth joint motion through the production of proteoglycan 4 (PRG4), also known as lubricin. Recent studies indicate novel effects of PRG4 as a signaling molecule, other than a simple extracellular matrix protein. Additionally, the accumulating evidence displays that various molecules and signaling pathways are involved in regulating the superficial zone and PRG4 expression. In addition, Prg4-expressing cells include a progenitor population of articular chondrocytes. Several non-clinical and clinical studies have shown that PRG4 and related molecules are promising candidates for disease-modifying drugs for treating osteoarthritis. Since PRG4 is also expressed in the synovium, tendons, and ligaments, further studies of PRG4-related pathways and PRG4-positive cells may elucidate the mechanisms underlying joint homeostasis.